PRODUCTION, PROCESSING AND CHARACTERIZATION TECHNIQUES FOR COSMIC DUST ANALOGUES - Rotundi A.; Palumbo P.; Brucato J.R.; Colangeli L.; Ferrini G.; Mennella V.; Palomba E. (My University, 2002)
The laboratory analyses of cosmic dust analogues—that in the context of this paper include interstellar, circumstellar as well as cometary dust—have a critical role in the study of circumstellar and cometary dust. The morphological, structural and chemical characterization of these analogues are critical for comparisons of their infrared and ultraviolet spectra with those obtained by astronomical observations, as well as for modeling purposes. Besides, the results from these laboratory studies are important to the success of space missions to comets when testing and calibrating the payload instruments. The interpretations of returned scientific data would benefit from the comparison with data recorded by the instruments in a laboratory setting for different classes of previously characterized analogues. We produced various types of condensed samples: (1) Mg,Fe-silicates, (olivine, pyroxene), (2) carbon-rich dust, and (3) mixed carbon-silicate dust. The samples were prepared using different techniques, viz. (1) laser bombardment of solid targets in an Ar and O2 atmosphere, (2) arc discharge in an Ar and H2 atmosphere, and (3) grinding powders of natural minerals. We simulated various post-condensation processes, such as thermal annealing, ultraviolet irradiation, ion bombardment and exposure to atomic hydrogen. These processes produced compound samples of a wide range of physico-chemical properties. To identify their textures, morphologies, grain compositions and crystallographic properties we used electron microscopy and far-ultraviolet to far-infrared (millimeter range) spectroscopy.